A Prisma-Based Systematic Review of How Artificial Intelligence Supports Teacher Pedagogical Comptence - M. Naufal Athallah; Saipul Annur; Gusti (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2025)
Teachers play a central role in ensuring meaningful learning processes, particularly through their pedagogical competence. At the same time, the rapid development of Artificial Intelligence (AI) is reshaping how lessons can be planned, delivered, and assessed. This study aims to synthesise empirical evidence on how AI is used to support teacher pedagogical competence in formal education settings. A systematic literature review was conducted following the PRISMA protocol using Scopus as the main database. Search, screening, and eligibility procedures were guided by predefined inclusion and exclusion criteria focusing on studies that reported the use of AI in relation to teachers’ pedagogical roles. Eight empirical articles met the criteria and were analysed thematically. The review shows that AI is mainly positioned as: (1) a companion for teaching, enriching instructional design and classroom activities; (2) a supporter of assessment and feedback through automation and learning analytics; and (3) a decision aid that informs teachers’ pedagogical choices. These findings highlight the need to strengthen teachers’ AI literacy and professional development so that AI can be integrated critically and responsibly to enhance, rather than replace, teacher pedagogical competence.